Performance Analysis of MIMO OFDM Transmission System using Adaptive MMSE with Iterative PIC Equalization - Shilpakar, Reeta; Baniya, Dinesh Chandra (Journal of Science and Technology, 2024)
The combination of multiple-input multiple-output (MIMO) signal processing with orthogonal frequency division multiplexing (OFDM) is regarded as a highly promising method to achieving the high data rates of next-generation wireless communication systems operating in frequency selective fading environments. This paper is focused on the usage of the adaptive Minimum Mean Square Error (MMSE) combined with Iterative Parallel Interference Cancellation (PIC) algorithm in MIMO OFDM transmission system to improve its bit error rate (BER). This paper uses multicarrier modulations such as BPSK, QPSK, 8-PSK and 16-QAM under AWGN and multipath fading environment i.e. Rayleigh channel. Simulation results show interesting gain in term of BER v/s SNR. These detectors improved the quality of received signal in high interference environment. Adaptive MMSE with iterative PIC give best performance in noise environment compared to MMSE, adaptive MMSE and iterative PIC.